Thin-film materials for solid-state rechargeable lithium batteries - Ribeiro, J. F. (2013)
Thin-film materials for solid-state rechargeable lithium batteries were fabricated by physical vapor deposition. The cathode is a lithium cobalt oxide (LiCoO2) film, separated from the anode (metallic lithium) by an electrolyte of lithium phosphorus oxynitride (LiPON). The LiCoO2 was deposited by RF sputtering, annealed after deposition and x-ray diffraction patterns showed higher crystallinity with 2 hours of annealing in vacuum with a temperature of 650 ºC. LiPON was deposited by reactive RF sputtering (nitrogen) and metallic lithium by thermal evaporation. Ionic conductivity of LiPON films was measured at room temperature of 26 ºC and 6.3x10-7 S.cm-1 obtained. Electrical resistivity of a 3 μm thickness lithium film was 7.6x10-8 Ω.m, measured during deposition.